Association of circulating serum free bioavailable and total vitamin D with cathelicidin levels among active TB patients and household contacts - Acen, Ester Lilian; Worodria, William; Kateete, David Patrick; Olum, Ronald; Joloba, Moses L.; Akintola, Ashraf; Bbuye, Mudarshiru; Biraro Andia, Irene (Research Square, 2022)
The free hormone hypothesis postulates that the estimation of free circulating 25(OH)D may be a better marker of vitamin D status and is of clinical importance compared to total vitamin D levels because it is the fraction involved in biological activities. Studies have shown that cathelicidin inhibits the growth of Mycobacterium Tuberculosis in a vitamin D-dependent manner and therefore adequate vitamin D is required for its expression. The aim of the study was to determine the association between serum-free and bioavailable and total vitamin D with LL-37 levels in ATB patients, LTBI and individuals with no TB infection. This was a cross sectional study and free and bioavailable vitamin D and LL-37 levels were measured. 95 specimens were further selected to estimate total vitamin D levels. The median free and bioavailable vitamin D levels of study participants were 3.8 ng/mL. The median LL-37 levels were 318.8 ng/mL. The mean total vitamin D levels were 18.9 ng/mL. Significantly weak inverse associations were found and vitamin D is involved in the regulation of LL-37 expression and low vitamin D levels can alter this relationship. Background Vitamin D deficiency is a prominent risk factor for TB disease worldwide (1–5). Vitamin D can be obtained in two forms, D2 is obtained through diet and D3 is obtained through skin biosynthesis (6). Its main circulating active metabolite 1, 25(OH)D is involved in regulation of antimicrobial activity and therefore important in TB therapy (7). So far, total vitamin D or 25(OH)D has been considered a better index for determining vitamin D status due to its longer half-life (6, 8–11). However, the free hormone hypothesis postulates that the estimation of free circulating 25(OH)D may be a better marker of vitamin D status and is of clinical importance compared to total vitamin D levels because it is the fraction involved in biological activities (10, 12–14). Bioavailable 25(OH)D is used to represent free vitamin D and the 10–15% fraction is loosely bound to albumin (8, 15). About 85–90% of total 25(OH)D is bound to VDBP and 10–15% is loosely bound to albumin and a small fraction remains unbound (13, 16). Free 25(OH)D is increased and readily available to cells when DBP levels are at low concentrations Previous studies report that changes in DBP levels and 25(OH)D binding affinity can lead to higher levels of free 25(OH)D, even in the absence of total vitamin D levels (17, 18). According to the Endocrine Society, total vitamin D status is classified into three groups: <20 ng/mL deficient, 21–29 ng/mL deficient, and > 30 ng/mL optimal; or sufficient amounts (19). In vitro and in vivo studies have shown that LL-37 inhibits the growth of MTB in a vitamin D-dependent manner (20, 21). Accordingly, studies have reported that adequate levels of 25(OH)D are required for expression of LL-37(22, 23). According to our systematic review, six studies reported that vitamin D regulates LL-37 expression and that vitamin D deficiency alters this function (24). Because the free fraction of vitamin D, which enters cells to cause biological effects, has not been studied with the LL-37 molecule, we hypothesize that there is no relationship between free and bioavailable vitamin D and total vitamin D with the LL-37 levels among the ATB patients, LTBI and individuals with no TB infection. This study aimed to determine the association between serum-free and bioavailable and total vitamin D with LL-37 levels in ATB patients, LTBI and individuals with no TB infection.
Keywords: Circulating serum free bioavailable; Vitamin D; Cathelicidin levels; TB patients